Introgression of productivity and other desirable traits from ricebean (Vigna umbellata) into black gram (Vigna mungo). Issue 4 (6th May 2013) - Singh, Inderjit; Sandhu, Jeet S.; Gupta, Shashi K.; Singh, Sarvjeet; Link, W.
Abstract Crosses were performed to introgress genes for productivity and other desirable traits from ricebean (Vigna umbellata) into black gram (Vigna mungo). Crossability was very poor in black gram × ricebean crosses, and only two to nine true hybrid plants were obtained. Plant fertility was very poor in initial generations, but was improved gradually from F2 onwards. Twenty‐four uniform progenies, bulked in F7, were evaluated for yield potential. The percentage increase/decrease in yield ranged from −35.48 to 50.31 over the check cultivar ('Mash338', female parent). All the progenies were found resistant to Mungbean yellow mosaic virus, Cercospora leaf spot and Bacterial leaf spot diseases. Overall, it was found that desirable traits such as high pod number, seed weight, productivity and resistance to diseases have been introgressed successfully into black gram from ricebean. A derivative line, KUG114, recorded yield superiority of 39.45% over the check cultivar 'Mash338' on the average of 14 multilocation research trials. It was released under the name 'Mash114' for cultivation in the Punjab state.